2017
DOI: 10.3389/fpsyg.2017.01970
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Them to Drive?—Parents' Reasons for Choosing the Car to Take Their Children to School

Abstract: Children's school journeys have changed vastly during recent decades: More children are being driven to school in private cars instead of walking and cycling, with many who are entitled to a free school bus service still being driven. Earlier research into travel mode choice has often investigated how urban form impacts upon mode choice regarding school journeys—in particular how urban form hinders or enables the use of the active mode. This paper quantitatively explores parents' stated reasons for choosing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 52 publications
(72 reference statements)
1
11
1
Order By: Relevance
“…Furthermore, Westman et al found associations between parent's reasons for driving their children to school and social convenience, showing that mode choice was mostly determined by practical reasoning and that parents wished to spend time with their children during travel [12]. Contrary to previous research, these authors found no associations of mode choice with safety or distance [12]. Taken together, this research displays an overall complex picture of parents' decisions, involving both personal and environmental aspects [13].…”
Section: Introductioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Furthermore, Westman et al found associations between parent's reasons for driving their children to school and social convenience, showing that mode choice was mostly determined by practical reasoning and that parents wished to spend time with their children during travel [12]. Contrary to previous research, these authors found no associations of mode choice with safety or distance [12]. Taken together, this research displays an overall complex picture of parents' decisions, involving both personal and environmental aspects [13].…”
Section: Introductioncontrasting
confidence: 49%
“…However, parents who drive their children perceive the environment as more dangerous, and other findings from intervention studies indicate that regular use of AST might decrease parents' perceived barriers [10,11]. Furthermore, Westman et al found associations between parent's reasons for driving their children to school and social convenience, showing that mode choice was mostly determined by practical reasoning and that parents wished to spend time with their children during travel [12]. Contrary to previous research, these authors found no associations of mode choice with safety or distance [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although SCCT is a well-established theory, the CSM model has recently been developed, and some of its relationships have not been tested yet. PLS-SEM has been utilized in the psychology literature (e.g., Westman et al, 2017), and also in career studies (e.g., Waters, 2004;Hsieh and Huang, 2014;Ren and Chadee, 2017). Its use is also recommended for estimating complex models that have many latent variables and indicators and test mediating effects as well as continuous moderator influences (Hair et al, 2017), as is the case here.…”
Section: Discussionmentioning
confidence: 99%
“…The highlighted agentive pathway in Figure 1 represents individual agency. Based on established research and the predominance of car-use in the US [5,20,[22][23][24][25], we expect this agentive pathway to be the defining feature of mobility as agency in the US. However, how does this choice connect to agency and environment in relation to alternative modes of transport, especially trains?…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In large parts of the country, low-density, sprawling communities are the norm [5,[19][20][21], and mobility of US Americans continues to be intertwined with private cars. Cars are synonymous with comfort [5], convenience [5,22], pleasure, freedom, satisfaction, and status [23][24][25]. According to Banister and colleagues [5] (p. 7), the car is culturally rooted: "Free roads, free parking, cheap petrol, and universal, cheap driver licensing are widely viewed as a natural right".…”
Section: Introductionmentioning
confidence: 99%